A fisiologia do prazer no Górgias de Platão : conjecturas acerca da presença de teorias da medicina hipocrática na reflexão platônica sobre o prazer - João Gabriel da Silva Conque Santos (2016)
Textual evidences allow us to consider the hypothesis that the conception of pleasure as a process of replenishment of a painful deficiency in Plato’s Gorgias could have been influenced by physiological theories developed in the medical treatise named Diseases IV, accredited to the hippocratic tradition. This dissertation proposes investigating in more detail this hypothesis once such enterprise can supply important elements for the understanding of the conception of pleasure in this dialogue as well as the value attributed to pleasure, especially in the discussion between the characters Socrates and Callicles. Therefore, we will initially contextualize the physiological description of pleasure presented by Plato in Gorgias and highlight the examples, the concepts and the terms involved in this same description. Next, we will try to understand, in a general way, how the hippocratic tradition deals with pleasure, looking to delimit, mainly, the vocabulary and the notions present in the physiological speech on the pleasure produced by the satisfaction of nutrition needs in Diseases IV. Finally, we intend to offer a comparison between the descriptions on pleasure in both texts in order to demonstrate that the platonic reflection in Gorgias on pleasure from examples involving hunger, thirst and the process of satisfying them, probably based in medical theories, is fundamental for the arguments offered by Socrates in his criticism to Callicles’s hedonism.